Model dan Strategi Penerapan Recyclable Art Boutique sebagai Wadah Edupreneurship Komunitas Pacitan Cerdas untuk Transformasi Limbah Menjadi Produk Kreatif dan Income Generating - Susanto, Hendra; Fitriyati, Umi; Witjoro, Agung; Wahyu Pratama, Ade; Nurul Izza, Jasmine (MES Bogor, 2025)
This research aims to develop a model and strategy for the implementation of Recyclable Art Boutique as a forum for edupreneurship of the Pacitan Cerdas community in optimizing the transformation of waste into creative products with economic value. The main focus is directed at strengthening the community's capacity in processing recycled waste into functional works of art that have marketability and have an impact on increasing local wisdom-based income. This research uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, which in this study is limited to the Development stage. The Analysis stage was carried out to identify waste potential, training needs, and community interest in recycling art-based entrepreneurship. The Design stage is focused on the preparation of learning models and strategies for the production, distribution, and branding of Recyclable Art. In the Development stage, a prototype of the Recyclable Art Boutique was developed in the form of training modules, product catalogs, digital marketing systems, and project-based learning plans. The results of the development show that this model has the potential to support community economic empowerment through a collaborative, sustainable, and educational approach.